(untitled) (Research, Society and Development, 2018)
Knowing how to deal with digital screens and new artifacts involves multiple skills and different intelligences. In this context, digital games are highlighted in order to identify how players perceive the exercise of multiple intelligences to contribute to the broadening of the understanding of the educational possibilities of using digital games. For that, an exploratory study of quantitative approach was carried out, through the application of a questionnaire with 58 students of the Distance Course in School Councils to evaluate the experience of using an educational game predicted as an activity. The results revealed, according to the students’ perception, that intelligence related to mathematics and logical reasoning was the most used, followed by existential intelligence, abstraction and spatial intelligence and motor coordination. This recognition of the exercise of multiple intelligences in the interaction with digital games reinforces their educational potential and the different pedagogical possibilities of use.